Electronic and electrochemical doping of graphene by surface adsorbates - Pinto, Hugo; Markevich, Alexander (Beilstein Journal of Nanotechnology, 2014)
Many potential applications of graphene require its precise and controllable doping with charge carriers. Being a two-dimensional material graphene is extremely sensitive to surface adsorbates, so its electronic properties can be effectively modified by deposition of different atoms and molecules. In this paper, we review two mechanisms of graphene doping by surface adsorbates, namely electronic and electrochemical doping. Although, electronic doping has been extensively studied and discussed in the literature, much less attention has been paid to electrochemical doping. This mechanism can, however, explain the doping of graphene by adsorbates for which no charge transfer is expected within the electronic doping model. In addition, electrochemical doping is in the origin of the hysteresis effects often observed in graphene-based field effect transistors when operating in the atmospheric environment.
Keywords: adsorbates; doping; electrochemical; electronic; graphene